Does Emotional Intelligence Drive Better Grades in Computer Studies? A Predictive Analysis - Jane Nkiruka Ozumba; Ebele Chinelo Okigbo; Emmanuel Chibuike Nwune (Scientia Publica Media, 2026)
The study investigated students’ emotional intelligence as a predictor of their achievement in Computer Studies in Awka Education Zone. The study was guided by two research questions and two hypotheses. It adopted the correlation survey research design on a population of 14,657 senior secondary two (SS2) students, out of which a sample of 390 students was obtained using Taro Yamane’s formula. However, only 335 (128 males and 207 females) students, representing 85.9% of the sample size, accurately completed the administered questionnaires and thus were used as the sample for the study. Emotional Intelligence Scale (EIS) with a Cronbach alpha reliability coefficient of 0.79 was used for collecting data for this study. Three experts from the Faculty of Education, Nnamdi Azikiwe University, Awka, validated the instrument. Data were collected by direct administration of the instruments to the students. Also, the second-term examination results of the students in Computer Studies for the 2023/2024 academic session were used as the achievement scores for the study. The data were analysed using the Pearson product-moment correlation Coefficient and regression analysis. The study’s findings revealed that emotional intelligence significantly predicted students’ academic achievement in Computer Studies. Also, the findings showed a moderating gender influence in the prediction in favour of the female students. The study’s findings imply that Computer studies teachers, as well as other educational stakeholders, should not just focus on helping students attain cognitive intelligence. These stakeholders should give emotional intelligence sufficient attention in the classroom, considering its significant role in predicting students’ academic achievement.